Evaluación de riesgos laborales por puestos de trabajo en el área de producción de la Empresa Productos Lácteos Guaytacama. - Parra Almachi, Carlos Santiago (2018)
Both evaluation and identification of laboral risks at workplace were carried out. This was based on laboral health and safety to improve the ongoing situation of the production area at Guaytacama dairy products company. Through this, physical, biological, chemical, mechanical, ergonomic and psicosocial risks were identified to subsequently bear in mind causes and consequences to take necessary and preventive measures to have a drop of the problem in a permanent way. In such matter, the company achieves the demand of legal requirements avoiding undesirable situations with continuous testing so as to warrant the health of every employee as well as condition of operating machines and good performance of productive procedures. This is all done to have the company succeed. Information and data extracted from different sources were used to identify and evaluate risks which many employees from the production area of the company get exposure to. The project also establishes a set of preventive measures which a businessman must keep in mind to abolish or reduce the risks as well as good Occupational Health and Safety and recommendations of usage for employees so as to have them work in a safer way.